Penerapan Model Group Investigation Berbantu Media Gambar Berseri Untuk Meningkatkan Keterampilan Menulis Siswa (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2020)
ABSTRACKÂ The purpose of this research is to describe the improvement of the writing skills of fifth grade students of SD 5 Jekulo Kudus on theme 6 by applying the Group Investigation learning model which is assisted by serial image media. The Group Investigation Model is a cooperative learning model that emphasizes student participation and activities to find their own material. Serial image media is a medium used to make it easier for students to understand learning. This class action research was carried out in class V with 29 students as research subjects which lasted for two cycles. Each cycle consists of two meetings and each meeting consists of four stages, namely planning, implementation, observation, and reflection. The results showed an increase in learning by applying the learning model in each meeting. Students' writing skills in pre-cycle obtained a percentage of 24.20% and increased in the first cycle by obtaining an average score of 752 with a percentage of 65.51% with a good category, experiencing an increase in the second cycle with an average score of 864 with a percentage of 89.65 % with very good category.Â Keywords: Group Investigation, Gambar Berseri, Keterampilan Menulis